2000
DOI: 10.1034/j.1600-0463.2000.d01-78.x
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal malformed lumbar vertebral corpora in trisomies 21, 18 and 13, evaluated radiographically and histologically

Abstract: The aim of the present study was to compare, both radiographically and histologically, malformed vertebral lumbar corpora in trisomies 21, 18 and 13 with earlier reported normal corporal development in the axial lumbar region. Axial skeletons of human fetuses (GA 15-22 wk) derived from therapeutically induced abortion were investigated in connection with requested autopsy. The number of lumbar vertebral corpora examined for each genotype was as follows: 20 from trisomy 21, 10 from trisomy 18, and 10 from triso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
7
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 15 publications
1
7
0
Order By: Relevance
“…radiographic finding in this genotype, as previously demonstrated [Kjaer et al, 1997b;Nolting et al, 2000]. The nature of vertebral clefting in autosomal aneuploidies remains obscure.…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…radiographic finding in this genotype, as previously demonstrated [Kjaer et al, 1997b;Nolting et al, 2000]. The nature of vertebral clefting in autosomal aneuploidies remains obscure.…”
Section: Discussionsupporting
confidence: 62%
“…Abnormal ossification patterns at both the radiographic and histological levels were previously documented in 40 fetuses with trisomies 21, 18, and 13 [Nolting et al, 2000], as well as eight fetuses with triploidy [Nolting et al, 2002]. Histologically, marked regional differences in metachromasia in the ground substance of the cartilage with Toluidine blue and Alcian blue/van Gieson stains was documented in all conditions.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Histological studies have demonstrated that pathological ossification of the vertebral corpora is associated with changes in metachromasia in ground substance of cartilage in trisomies 21, 18 and 13 (11).…”
mentioning
confidence: 99%
“…Polymorphisms in these genes, however, are not significantly associated with NTDs in all populations, suggesting that polygenic and environmental factors are important. Our groups and others have described NTDs in chromosomal and inherited syndromes, including trisomy 13 (13)(14)(15)(16), trisomy 18 (16 -19), trisomy 21, and 22q11.2 and 13q deletion syndromes (20)(21)(22)(23). In rare cases, syndromes that variably present with NTDs have been associated with a mutation in a single gene (24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36).…”
Section: Introductionmentioning
confidence: 99%